CLARITY AND ACCESSIBILITY AS DRIVERS OF SCIENTIFIC IMPACT IN ACADEMIC WRITING (Scientific journal of the Fergana State University, 2026)
This article explores how conceptual theories of scientific discourse shape clarity, accessibility, and impact in peer-reviewed academic writing. Using a discourse analysis approach, it investigates semantic strategies and structural conventions that enhance scientific communication. The study emphasizes the importance of plain language, open access, and legal frameworks - particularly within the context of Uzbekistan. Findings highlight that clarity and accessibility are not stylistic options but essential tools for increasing research visibility, academic collaboration, and policy influence.